Detection of Airborne Lactococcal Bacteriophages in Cheese Manufacturing Plants - Verreault, Daniel (American Society for Microbiology (ASM), 2011)
The dairy industry adds starter bacterial cultures to heat-treated milk to control the fermentation process during the manufacture of many cheeses. These highly concentrated bacterial populations are susceptible to virulent phages that are ubiquitous in cheese factories. In this study, the dissemination of these phages by the airborne route and their presence on working surfaces were investigated in a cheese factory. Several surfaces were swabbed, and five air samplers (polytetrafluoroethylene filter, polycarbonate filter, BioSampler, Coriolis cyclone sampler, and NIOSH two-stage cyclone bioaerosol personal sampler) were tested. Samples were then analyzed for the presence of two Lactococcus lactis phage groups (936 and c2), and quantification was done by quantitative PCR (qPCR). Both lactococcal phage groups were found on most swabbed surfaces, while airborne phages were detected at concentrations of at least 10(3) genomes/m(3) of air. The NIOSH sampler had the highest rate of air samples with detectable levels of lactococcal phages. This study demonstrates that virulent phages can circulate through the air and that they are ubiquitous in cheese manufacturing facilities.